Pickering emulsions with low interface coverage but enhanced stability for emulsion interface catalysis and SERS-based detection - Mingkun Li; Qing Song; Yilin Wang; Bing Liu (Nature Communications)
Abstract Particle adsorption at the oil-water interface is an important strategy for emulsion stabilization against coalescence, however, the particle occupation of the interface and the requirement of free interfaces in many applications is a contradiction. We report an emulsion type with low droplet surface coverage but enhanced stability by employing colloidal rings as emulsifiers. The formed emulsions provide a large accessible oil-water interface (>80%). The enhanced diffusion through the interface and highly efficient loading of catalytic nanoparticles at the interface result in much higher catalytic efficiency than the nanosphere-covered emulsions in both batch and continuous flow interface catalysis. The loading of plasmonic nanoparticles brings excellent performance in surface-enhanced Raman spectroscopy-based detection, which exhibits the lowest detectable concentration as low as 10−11 M using only 0.25 μL of analyte and 0.2 μg of Au nanoparticles. The ring-based Pickering emulsion provides freedom for designing interface structures and compositions for functional emulsions.